Striatal and cerebellar interactions during reward-based motor performance - Joonhee Leo Lee; Agostina Casamento-Moran; Amy J. Bastian; Kathleen E. Cullen; Vikram S. Chib (Proceedings of the National Academy of Sciences, 2025)
Goal-directed motor performance relies on the brain’s ability to distinguish between actions that lead to successful and unsuccessful outcomes. The basal ganglia (BG) and cerebellum (CBL) are integral for processing performance outcomes, yet their functional interactions remain underexplored. We scanned participants’ brains with functional magnetic imaging (fMRI) while they performed a skilled motor task for monetary rewards, where outcomes depended on their motor performance and probabilistic events that were not contingent on their performance. Successful motor outcomes increased activity in the ventral striatum (VS), a functional subregion of the BG, whereas unsuccessful motor outcomes engaged the CBL. In contrast, for probabilistic outcomes unrelated to motor performance, the BG and CBL exhibited no differences in activity between successful and unsuccessful outcomes. Dynamic causal modeling revealed that VS-to-CBL connectivity was inhibitory following successful motor outcomes, suggesting that the VS may suppress CBL error processing for correct actions. Conversely, CBL-to-VS connectivity was inhibitory after unsuccessful motor outcomes, potentially preventing reinforcement of erroneous actions. Additionally, interindividual differences in task preference, assessed by having participants choose between performing the motor task or flipping a coin for monetary rewards, were related to inhibitory VS-CBL connectivity. These findings highlight a performance-mediated functional network between the VS and CBL, modulated by motivation and subjective preferences, that supports goal-directed behavior.